2012
DOI: 10.4103/2230-8210.98007
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and the oral cavity

Abstract: Menopause is associated with a large number of symptoms ranging from physical to psychological. These symptoms may unfavorably affect oral health and treatment needs requiring dentists to be aware of the symptoms and health care needs of peri-menopausal/menopausal/postmenopausal women. This article attempts to provide an insight into the multifarious oral manifestations at menopause along with the relevant prosthodontic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
0
8
0
3
Order By: Relevance
“…Women taking hormone therapy may not experience oral problems as readily as their untreated counterparts, although hormone therapy has mixed results depending on the oral systemic health of each individual. Several studies have indicated that estrogen therapy protects against mandibular bone loss and diminishes the severity of periodontal disease in postmenopausal women (Haskin & Mobley, 2013;Mutneja, Dhawan, Raina, & Sharma, 2012).…”
Section: Menopausementioning
confidence: 99%
See 1 more Smart Citation
“…Women taking hormone therapy may not experience oral problems as readily as their untreated counterparts, although hormone therapy has mixed results depending on the oral systemic health of each individual. Several studies have indicated that estrogen therapy protects against mandibular bone loss and diminishes the severity of periodontal disease in postmenopausal women (Haskin & Mobley, 2013;Mutneja, Dhawan, Raina, & Sharma, 2012).…”
Section: Menopausementioning
confidence: 99%
“…The decrease in estrogen contributes to the drying of the oral mucosa and can lead to menopausal gingivostomatitis, which is characterized by gingiva that bleed readily, with an abnormally pale dry/shiny erythematous appearance (Mutneja et al, 2012). Unchecked, gingivitis leads to periodontitis.…”
Section: Menopausementioning
confidence: 99%
“…Such disorders have a tendency to influence impression-making procedures, recording jaw relations, and denture retention. [ 40 ] Thus, strategic protocols are suggested to menopausal women to reduce anxiety and stress during treatment procedures.…”
Section: Selection Of Datamentioning
confidence: 99%
“…Menopausal women having eating disorders may suffer from smooth erosion of enamel, perimolysis, increased tendency to use pen and combs to induce vomiting, enlarged parotid glands, angular cheilitis, dehydration, erythema, and trauma to the oral mucosa and pharynx resulting from use of fingers. [ 40 ]…”
Section: Selection Of Datamentioning
confidence: 99%
“…Thus, employment of anxiety and stress reduction protocols are suggested in menopausal women during treatment procedures. [ 13 14 ]…”
mentioning
confidence: 99%